1
$\begingroup$

This is a homework problem that I just can't make progress on. I know that it can be shown through a special case of the generalized arithmetic-geometric mean inequality ($a^t b^{1-t} \leq ta + (1-t) b$), but I just can't choose variables correctly. Hoping for a hint, not a solution. I've tried setting $t = \sin^2 x$, $a = \sin x$, $b = \cos x$ (so $1-t = \cos^2 x$), and several permutations of these, but I'm getting nowhere.

$\endgroup$
4
  • 2
    $\begingroup$ Just prove that $\sin x < \cos x$ for $0 < x< \pi/4$. $\endgroup$ – minori minus May 15 '19 at 1:04
  • $\begingroup$ that's not enough since the powers go the other way, namely $(\sin x)^{\sin x} > (\sin x)^{\cos x}$ and same with $(\cos x)^{\sin x} >(\cos x)^{\cos x}$; note that at $0$ both terms converge to $1$, while at the other end again both terms are equal, so there can't be any simple monotonicity $\endgroup$ – Conrad May 15 '19 at 1:08
  • $\begingroup$ $$\sin x-\cos x=\sqrt2\sin(x-\pi/4)$$ and $$\sin x,\cos x>0$$ $\endgroup$ – lab bhattacharjee May 15 '19 at 1:12
  • $\begingroup$ Take $f(x)=x^x$ and $f'(x)=x^x(1+\ln(x))<0$,. So $f(x)$ is increasing in $(0,e^{-1}]$.This means that $f(x)$ is both increasing and decreasing in .$[0,1/\sqrt{2}].$ So use of $x^x$ doesn't really help here and this makes the proof of Conard using a mix of AM-GM and calculus is valuable. $\endgroup$ – Z Ahmed May 15 '19 at 2:11
3
$\begingroup$

$t=\frac{\sin x}{\cos x}, 1-t=\frac{\cos x-\sin x}{\cos x}, a=\sin x, b=\cos x+\sin x$

Since $0<x<\frac{\pi}{4}$, we get $0<t<1, b=\frac{2}{\sqrt 2}\cos (\frac{\pi}{4}-x) > 1$

$a^t b^{1-t} \leq ta + (1-t) b$ translates to

$(\sin x)^{\frac{\sin x}{\cos x}}b^{1-t} \le \cos x $.

Raising the above to power $\cos x$ and noting that $b>1, 1-t>0$, so $b^{\frac{1-t}{\cos x}}>1$, we get

$(\sin x)^{\sin x}<(\sin x)^{\sin x}b^{\frac{1-t}{\cos x}} \le (\cos x)^{\cos x}$, so done

$\endgroup$
1
$\begingroup$

Let $F(x)=x^{1/\sqrt{1-x^2}}$ for $x \in (0,1).$ $$\frac{f'(x)}{f(x)}=\frac{1-x^2+x^2 \ln x}{x (1-x^2)^{3/2}}$$ Now let $g(x)=1-x^2+x^2 \ln x$, $g'(x)= x(\ln x^2-1)<0,$ for $x \in (0,1].$ $g(x)$ is a decreasing function $g(x) >g(1)=0$, therefore $f'(x)>0$, $f(x$) is an increasing function. Finally, $$ \sin x < \cos x,~ \mbox{for}~ x \in [0,\pi/4] \Rightarrow f(\sin x) < f(\cos x) \Rightarrow (\sin x) ^{\sec x} <(\cos )x^{\csc x} \Rightarrow (\sin x)^{\sin x} < (\cos x)^{\cos x}.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.